Debating German cultural identity since 1989 - Fuchs, Anne; James-Chakraborty, Kathleen, 1960-; Shortt, Linda (Studies in German literature, linguistics, and culture., 2011)
The events of 1989 and German unification were seismic historical moments. Although 1989 appeared to signify a healing of the war-torn history of the twentieth century, unification posed the question of German cultural identity afresh. Politicians, historians, writers, filmmakers, architects, and the wider public engaged in ""memory contests"" over such questions as the legitimacy of alternative biographies, West German hegemony, and the normalization of German history. This dynamic, contested, and still ongoing transformation of German cultural identity is the topic of this volume of new essa